The trans-10, cis-12 isomer of conjugated linoleic acid decreases adiponectin assembly by PPARγ-dependent and PPARγ-independent mechanisms - Miller, Jessica R. (2008)
The adipocyte-derived secretory protein adiponectin functions as an insulin-sensitizing agent. In plasma, adiponectin exists as low, medium, and high molecular weight oligomers. Treatment with trans-10, cis-12 conjugated linoleic acid (t-10, c-12 CLA) reduces levels of adiponectin as well as triglyceride (TG) in mice and adipocyte cell culture models. The aim of this study was to determine whether the effects of t-10, c-12 CLA on adiponectin and TG are mediated through modulation of the transcription factor peroxisome proliferator-activated receptor γ (PPARγ). 3T3-L1 cells were treated either during or after differentiation into adipocytes with 100 μM t-10, c-12 CLA with or without 10 μM troglitazone, a PPARγ agonist, or 1 μM GW9662, a PPARγ antagonist, and adiponectin and TG levels were analyzed. Treatment with t-10, c-12 CLA reduced TG as well as cellular and secreted adiponectin levels and impaired the assembly of adiponectin oligomers. These changes were accompanied by decreases in PPARγ mass. Troglitazone was able to reverse the t-10, c-12 CLA-mediated decrease in TG levels and restore the assembly of adiponectin oligomers but was unable to restore adiponectin synthesis. Conversely, treatment with GW9662 decreased TG mass and impaired adiponectin oligomer assembly but did not decrease total adiponectin mass. In a reporter assay, t-10, c-12 CLA appeared to be a partial PPARγ agonist and prevented the stimulation of reporter activity by troglitazone. Therefore, the t-10, c-12 CLA isomer appears to alter adipocyte adiponectin metabolism through PPARγ-dependent and PPARγ-independent mechanisms.